Developing An Electronic Module Based on Local Wisdom in Dokan Village to Optimize the Character Education - Adiatmana, Donny; Hasan, Muhammad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The research aims to develop an electronic module that contains the local wisdom in Dokan Village. Nowadays, character education is needed to create a generation that has cooperation, togetherness, and caring for each other and thus local wisdom has values that can be used to teach character education. This research is research and development (R&D) with the 4 D design proposed by Sivasailam Thiagarajan. 4 D design consists of define, design, development, and dissemination. The research involved experts in learning media, Karo culture, and language to assess the electronic module. The sample is fourth-semester students in English Department Study Program, STKIP Al Maksum. The research used one group pre-test post-test to know the influence of the electronic module in teaching character education to the students. Based on the discussion, the expert in learning media, Karo culture, and language was assessed electronically in the two stages. In the first stage, the electronic module was invalid the score range was 58%. In the second stage, the electronic module was valid the score range was 90%. Furthermore, based on the t-test, the electronic module was effective to teach character education to the students.